How to Explain the Rationale of Putting Research into Practice? A Book Review on Visual-Spatial Ability in STEM Education Transforming Research into Practice - Baskota, Prateet (Journal of Transformative Praxis, 2023)
The book is crucial for exposing educational settings to research academics since it is visually appealing. It explains how spatial ability is tested and improved and explores the research procedures and skills utilized in educational settings. It concentrates on the problematic meta-analytic review and addresses two distinct cross-questions, including how large gender disparities in spatial ability are and where gender differences in spatial ability are first observed. The book purposefully covers a wide range of viewpoints, including those from cognitive psychology, educational psychology, science, technology, engineering, mathematics, computer science and information technology. It also addresses human growth. This book gives ideas about the early life span of visuospatial working memory development, along with the impact. As a reader, I found that these abilities have on academic learning with a biological explanation for the observed gender differences that seems to be a contribution to brain development that was shared through the book by the author for readers.